Prosedur Pengurusan Rencana Pengoperasian Kapal (RPK) Menggunakan Sistem SIMLALA Oleh PT. Dian Bahari Perkasa Dumai - Nanda Tri Wulandari; Syarifur Ridho; Yuna Sutria (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
This paper aims to describe the Procedure for Managing Ship Operation Plans (RPK) using the SIMLALA System implemented by PT. Dian Bahari Perkasa Dumai. This research uses field research and library research methods. The RPK processing process through the SIMLALA system has been running smoothly, starting with a submission from the shipping company appointed by the ship owner to manage the RPK. The ship agent then attaches all the documents and requirements needed to submit the RPK via the SIMLALA system. After that, officers from the Harbormaster's Office and Port Authority checked the documents that had been uploaded to the system. If all documents have been checked, the Harbor Master's Office and Port Authority can issue a Ship Operation Plan (RPK) certificate through the SIMLALA System.